2017
DOI: 10.5194/bg-14-1527-2017
|View full text |Cite
|
Sign up to set email alerts
|

New insights on resource stoichiometry: assessing availability of carbon, nitrogen, and phosphorus to bacterioplankton

Abstract: Abstract. Boreal lake and river ecosystems receive large quantities of organic nutrients and carbon (C) from their catchments. How bacterioplankton respond to these inputs is not well understood, in part because we base our understanding and predictions on "total pools", yet we know little about the stoichiometry of bioavailable elements within organic matter. We designed bioassays with the purpose of exhausting the pools of readily bioavailable dissolved organic carbon (BDOC), bioavailable dissolved nitrogen … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 56 publications
8
41
0
Order By: Relevance
“…In a Baltic Sea study, the DOP pool was 75% bioavailable (Stepanauskas et al, 2002) and a similar value (33.2-60%) was reported for 3 stations in the central Baltic as part of a different study (Nausch and Nausch, 2007). A more recent analysis suggested that ∼40% of the DOP in four boreal lakes was bioavailable (Soares et al, 2017). Our study of 27 unique systems supports the idea of very labile BDOP with a median value of ∼78%, but also highlights the large amount of variability in BDOP across systems.…”
Section: Bioavailability Of Doc and Dopsupporting
confidence: 63%
See 2 more Smart Citations
“…In a Baltic Sea study, the DOP pool was 75% bioavailable (Stepanauskas et al, 2002) and a similar value (33.2-60%) was reported for 3 stations in the central Baltic as part of a different study (Nausch and Nausch, 2007). A more recent analysis suggested that ∼40% of the DOP in four boreal lakes was bioavailable (Soares et al, 2017). Our study of 27 unique systems supports the idea of very labile BDOP with a median value of ∼78%, but also highlights the large amount of variability in BDOP across systems.…”
Section: Bioavailability Of Doc and Dopsupporting
confidence: 63%
“…However, a fundamental problem associated with understanding these imbalances is our capacity to know what the resource availability is that organisms actually experience. Our ability to accurately describe the resource imbalance experienced by bacterial communities in situ is hindered by our lack of simultaneous measurements of the bioavailability of multiple elements (Berggren et al, 2014;Soares et al, 2017). Here, we observed that the experienced BDOC:BDOP resource ratios of aquatic bacterial communities were typically less than measured DOC:DOP pools (Figure 11).…”
Section: Stoichiometry Of Bioavailable Nutrientsmentioning
confidence: 88%
See 1 more Smart Citation
“…Although protozoa were not removed, based on Daniel et al (2005) it can be assumed that bacteria vastly dominate the biomass (∼ 90 %) when dark bioassays are performed on natural humic water. We assumed that there was no nitrogen or phosphorus limitation due to the high concentrations of DOC (∼ 15 mg L −1 ) known to be associated with high organic nutrient bioavailability in lakes (Soares et al, 2017) and streams of the region. Our assumption is supported by Jansson et al (2001), who showed that bacterial metabolism in humic lakes is generally not nutrient limited when DOC is higher than ∼ 15 mg L −1 .…”
Section: Laboratory Experimentsmentioning
confidence: 99%
“…Empirically, BP has been shown to increase with P concentrations in a wide range of low- and high-productive surface waters [50, 51], but results from correlational studies are not consistent [52]. Often, the identification of P as main regulator of BP is hindered by the fact that the export of terrestrially derived DOC co-occurs with that of inorganic and organic P [9, 53], both of which are known to be highly bioavailable at Baltic Sea river mouths [54]. A large number of studies have addressed the direct effects of increasing DOC on aquatic ecosystems, but increased P fluxes driven by the increase in riverine DOM exports are often neglected [55].…”
Section: Discussionmentioning
confidence: 99%